Impact of cytokines on the pathomechanism of diabetic and alcoholic neuropathies - Michałowska-Wender, Grażyna; Adamcewicz, Grażyna; Wender, Mieczysław (Folia Neuropathologica, 2007)
Diabetic and alcoholic neuropathies are heterogeneous groups with variable lesions of axons or myelin. Their pathogenesis is complex and involves multiple pathways. To elucidate the impact of immunological factors in development of these neuropathies the expression of some cytokines in serum was studied: tumour necrosis factor a (TNF-a), monocyte chemotactic protein-1 (MCP-1) and growth-regulated oncogene alpha (GRO-α; CXCL1). 29 patients with type 2 diabetes, 31 with chronic alcohol abuse and 20 healthy controls were included in the study. The type of neuropathy (involvement of axon or myelin) was evaluated by electrophysiological methods (EMG and nerve conduction velocity). The cytokine level was determined by ELISA method. For statistical comparison the nonparametric Mann-Whitney test was used. The evaluated material was divided according to clinical duration of neuropathy and electrophysiological pattern. Expression of TNF-α in both types of neuropathy does not differ from the control material. Expression of MCP-1 was higher, but insignificantly, in patients with alcoholic neuropathy. The same concerns the demyelinating form versus axonal diabetic neuropathy. Serum level of GRO-α; was significantly higher in patients with alcoholic neuropathy and in cases with demyelinating form of diabetic neuropathy than in control subjects. GRO-α; is a potent neutrophil chemoattractant playing an important role in various primary and secondary inflammatory processes. The results suggest that GRO-α; may contribute to the mechanism of alcoholic neuropathy and in demyelinating form of diabetic neuropathy.